2017
DOI: 10.1126/sciadv.1603210
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of aqueous solutions: Bridging the gap between theory and experiments

Abstract: A predictive and efficient computational framework for describing the electronic properties of aqueous solutions is presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
66
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 72 publications
7
66
0
Order By: Relevance
“…In order to validate our computational protocol, we first compared the energies computed for the occupied electronic states of water with well-established liquid jet experimental data 13 , 36 . Consistent with our previous studies 37 , 38 , we found that the most accurate protocol for computing the binding energies of electrons in water is the G 0 W 0 approximation based on dielectric-dependent hybrid (DDH) functionals 39 , 40 . In particular, G 0 W 0 calculations with the range-separated hybrid (RSH) yielded a mean absolute error (MAE) with respect to measured spectra of only 0.18 eV for trajectories including nuclear quantum effects (NQE) and 0.38 eV for classical trajectories.…”
Section: Resultssupporting
confidence: 87%
“…In order to validate our computational protocol, we first compared the energies computed for the occupied electronic states of water with well-established liquid jet experimental data 13 , 36 . Consistent with our previous studies 37 , 38 , we found that the most accurate protocol for computing the binding energies of electrons in water is the G 0 W 0 approximation based on dielectric-dependent hybrid (DDH) functionals 39 , 40 . In particular, G 0 W 0 calculations with the range-separated hybrid (RSH) yielded a mean absolute error (MAE) with respect to measured spectra of only 0.18 eV for trajectories including nuclear quantum effects (NQE) and 0.38 eV for classical trajectories.…”
Section: Resultssupporting
confidence: 87%
“…One of the problems of Li-S battery, the shuttle effect, is caused by the dissolution of lithium polysulfide (Li2Sy, 4 ≤ y ≤ 8) in the solvent. However, it is a long-standing challenge to theoretically predict the solvent behaviors of polysulfide and to calculate the solvated Gibbs formation energies of these polysulfide [19,30] . In our calculation, the charge polarizable solvent model with a fixed ion charge to determine the dielectric function profile, is used to represent the solvent effect.…”
Section: Computation Detailsmentioning
confidence: 99%
“…Thus, one has to search for the global minimum structures. The effects of solvent further complicate the issue [19] . .…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless periodic DFT calculations with hybrid functionals and PW basis sets remain substantially heavier, from a computational standpoint, than local or semi-local DFT calculations. The functionals PBE0 [42] and HSE [43][44][45] are among the most popular hybrid functionals used for condensed systems, and lately dielectric dependent hybrid functionals [46][47][48][49] have been increasingly used to predict structural and electronic properties of solids [46,47,[49][50][51][52][53][54][55][56][57] and liquid [58][59][60] and of several molecules [47,48,61]. Another category of orbital dependent functionals recently proposed is that of Koopmans-compliant functionals, used for both molecules and solids [62][63][64].…”
Section: Introductionmentioning
confidence: 99%